Empowering The Limo Urban Village Community in Depok City Through Plastic Waste Recycle Training as an Entrepreneurial Alternative - Sigit Pradana; Erna Hernawati; Retna Sari; Budhi Martana (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2024)
The service program for community groups in the Limo area, Limo Subdistrict, Depok City, focused on training plastic waste recycling management in environmental care communities that were not yet productive or had no regular income. The problems faced include a waste segregation system that had not been maximized, less than optimal plastic waste management, lack of plastic waste processing technology, and low creation of recycled plastic waste-based products. The purpose of this program was to provide training in making products based on recycled plastic waste as an effort to reduce plastic waste and as an alternative to entrepreneurship. The program implementation was carried out through Focus Group Discussions with partners, knowledge sharing, training on plastic waste processing technology, and the practice of making recycled products. The technology introduced includes a plastic shredder and a simple printing press. The results of the program showed active participation of participants, increased knowledge of plastic waste processing with an achievement rate of 90%, and recycled product manufacturing skills reaching 80%, indicating the success of the program in increasing community awareness, skills, and entrepreneurship in plastic waste management.